PERAN ORANG TUA DALAM MEMINIMALISIR PENGGUNAAN GADGET PADA ANAK USIA 3-6 TAHUN - Nurul Aenun Adlia; A. Nurhayati; Muhammad Irham Zainuri (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study discusses the role of parents in reducing gadget use among children aged 3–6 years in Kombong Village, Bua District. The phenomenon of increasing gadget use among young children raises concerns about negative impacts on physical, social, emotional, and cognitive development. This study uses a qualitative method with a phenomenological approach to explore the experiences and views of parents. The research subjects were seven parents selected through purposive sampling, with the criterion of having children aged 3–6 years who use gadgets. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The results of the study indicate that parents play a role through direct supervision, regulating usage duration, and monitoring the content accessed by children. The strategies employed include encouraging children to play with peers, providing educational games, gardening, reading books, drawing, and engaging in outdoor activities. This approach effectively diverts children's attention from gadgets, enhances social skills, and reduces the risk of addiction. These findings underscore the importance of active parental involvement in maintaining a balance between technology use and children's development.